Learner’s Mathematical Conceptual Understanding and Its Relation to The Mathematical Communication Skills - Joko Krismanto Harianja; Sarah Lorin Hernadi; Isabela Indah (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2020)
ABSTRACTThis research was basically conducted to improve students’ understanding of mathematical concepts and mathematical communication skills both verbally and non-verbally using the Rally Coach learning method. In addition, the main purpose of this study is to examine and analyze the relationship between students’ understanding mathematical concepts and mathematical communication. Therefore, the authors first design instruments to measure students’ understanding of mathematical concepts and mathematical communication skills that have been adapted to indicators. This study is based on correlational research method. The instrument was tested to see its validity and reliability using the Cronbach Alpha formula. The results show that the application of the Rally Coach learning model has a positive influence in improving students’ understanding of mathematical concepts and mathematical communication. The results of the analysis by statistical testing with Pearson correlation show that there is a relationship between understanding mathematical conception and mathematical communication skills, but the relationship is not so strong. This can be seen from observations made by authors, some students are able to understand mathematical problems, but are not fully able to communicate verbally.Keywords: mathematical communication; mathematical conceptual understanding; Pearson correlation; rally coach; validity and reliability test.